Concomitance of oligotrophy and low grazing pressure is essential for the resilience of Mediterranean subtidal forests. Issue 1 (15th October 2017) - Piazzi, Luigi; Ceccherelli, Giulia
Abstract: The study aimed at investigating factors influencing the recovery of the canopy seaweed Cystoseira brachycarpa . A manipulative experiment was done to test if in barren patches the recovery of Cystoseira I) is enhanced by the removal of the urchins, II) is prevented by eutrophication, III) depends on the time of patch clearance and IV) decreases with the distance from Cystoseira bed edge within the barren patch. The effects of the same factors on the structure of the macroalgal assemblage were also tested. Cystoseira recovered abundantly only in clearings where nutrients were not added and urchins were removed. Furthermore, Cystoseira recovered irrespectively of the time the patches were cleared and the distance from the canopy edge. This study showed that the lack of sea urchins at oligotrophic conditions was essential for Cystoseira brachycarpa recruitment, providing evidence that interacting constraints are involved in the recovery of Cystoseira beds. Highlights: The recovery of the canopy seaweed Cystoseira brachycarpa was investigated. The herbivore pressure and nutrient regime were experimentally manipulated. Cystoseira recruited where nutrients were not added and urchins were removed. Cystoseira recovered irrespectively of the time that patches were cleared. Cystoseira recovered irrespectively of the distance from the canopy edge.